SPEECH ACTS CATEGORIES: AN ANALYSIS OF CHARACTERS’ UTTERANCES IN “BEAUTY AND THE BEAST” - Tanjung, Firima Zona (Universitas PGRI Sumatera Barat, 2019)
This study aims at analyzing speech acts in the dialogue conducted among characters in “Beauty and The Beast” movie and the implication of analysis for teaching English in EFL context. Qualitative and quantitative methods were employed in order to process the data comprehensively. Movie script and movie video were exploited as the source of data. The procedure of analysis was conducted through identification, classification, and utilization of comprehensive analysis of language use in relation to pragmatics and contexts in discourse approach. The findings showed that all type of speech acts were used by all characters in their dialogue. Among types of speech acts, directive speech act was frequently employed since it reached 92 times of use (57%). Particularly, the analysis of speech acts in characters’ utterances can benefit teaching practitioners mainly in making connection of using movie as learning media with the teaching of language in EFL setting. Therefore, students do not only watch the movie but they also learn the language simultaneously.